Demand-side resource response characteristics and peak shaving scheduling response model - Weijia Guo; Dunnan Liu; Mingguang Liu; Huiling Zhang; Guobin Wang; Bo Fan; Wentao Xu (Energy Reports, 2022)
Demand-side resources have significant meaning in load regulation. However, these resources have different response characteristics, which will greatly affect the efficiency of load regulation. By analyzing the characteristics of different demand-side resources, this paper trying to summarize the response modeling for different types of demand-side resources. Then establish a scheduling-response mode, which takes optimal peak shaving response as its goal and takes the power and electricity quantity as the constraint conditions to solve the model. Finally, this paper carries out a practical example to evaluate the peak shaving effect of this model. By using this model, the peak load in the example is reduced by 5.29% and the valley load is increased by 5.31%, which verify this response model can promote the effectivity of dispatching without interfering the basic power demand of users.